The effect of Look-Up technique on speaking fluency - Achlia Niza Ayunda (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2012)
This research is conducted to find an effective technique to teach speaking of second semester students. To collect the data, this research using pre- and post-test. The treatment is look-up technique in which the learners work in pairs facing each other. One is the reader, the other is the listener. The reader holds the book containing the dialogue at about chest level and slightly to the left. This enables the reader to look at the book and then look at the listener, moving only her eyes and not having to move her head at all. The reader looks at the book and tries to remember as long a phrase as possible. The reader can look at the book for as long as is necessary. Then, when ready, she/he looks at the listener and says the phrase. While she/he speaks, she/he does not look at the book. These rules force the reader to rely on memory. To analyze the data gained from post-test for both control and experimental class, the researcher used the t-test formula. The findings showed that t-value higher than t-critical, 1,671 <5.8> 2,390 which means that Null Hypothesis (Ho) was rejected. Thus, it can be concluded that it is effective to use look up technique in teaching English speaking, because the research hypothesis (H1) which says “there is a difference in speaking skill between students who were taught using look-up technique and those who were taught using conventional technique (role-play) in their speaking class” was accepted.